Determinants affecting student engagement in online learning: examining teaching styles and students’ computer self-efficacy / Mohammad Alzahrani ... [et al.] - Alzahrani, Mohammad; Alrashed, Yousef; Jdaitawi, Malek; Abdulghani, Samah; Nasr, Nahed; Ghanem, Reham; Kholif, Marwa (Universiti Teknologi MARA, 2023)
Implementation of modern technologies has been suggested to enhance student learning. The purpose of this study is to investigate the determinants of student engagement in online learning with regards to teaching styles and computer self-efficacy. A descriptive cross-sectional design was employed using a survey method to collect data from 265 respondents in Jordan during the academic year 2022-2023. The results revealed that teaching styles significantly affect students' engagement in online learning while students’ computer self-efficacy does not have a significant impact. As there are only a few studies on factors that negatively impact student engagement in online learning settings, this study addresses the gap in literature on online learning environments. The results provide practical information for academic administrators, computer instructors, and students. Through highlighting the interplay between the various online variables and students’ engagement in Jordan, this study can assist stakeholders in designing professional development training sessions, programmes, or manuals to equip students and instructors with the necessary knowledge and skills related to integrating technology into their daily teaching and learning activities. The study recommends that future studies explore other personal, environmental and cognitive factors as well as involve larger samples of students from several public and private universities in Jordan.